Miliary Tuberculosis and Infective Endocarditis - Harshil Gumasana; Mansukh V Patel (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Background: Miliary Tuberculosis (MTB) is a potentially lethal disease if not diagnosed and treated early. Miliary tuberculosis infection in childhood remains a significant health problem in developing countries. Clinical manifestations are non-specific and therefore the condition may bemuse even the most experienced clinicians. Infective Endocarditis (IE) remains a lethal valvular heart disease and can be fatal if not treated promptly. Coagulase-negative staphylococci and oral streptococci are common causative organisms. Both conditions can be fatal independently but can present in the same patient. Since fever is a common symptom in both, one infection may mask the other. Tuberculous Endocarditis (TBE) is another rare entity with few documented cases and often presents with a miliary tuberculosis picture, especially in endemic countries. Case presentation: We report the case of a 9-year-old immunocompetent girl who presented with history of congenital heart disease, fever, malaise, and anemia for a duration of two months. Transthoracic Echocardiography (TTE) revealed a 10x7mm vegetation on the anterior mitral valve leaflet along with Mitral Stenosis (MS) mild Mitral Regurgitation (MR) and a Patent Ductus Arteriosus (PDA). Blood cultures grew streptococcus viridans. She was started on broad spectrum antibiotics but continued to be febrile along with drenching night sweats. Chest CT was consistent with miliary tuberculosis and a subsequent sputum for GeneXpert® test was positive. She was subsequently started on Anti-Tubercular Treatment (ATT). An eight week follow up showed resolution of the vegetation, improvement in symptoms, resolution of anemia and weight gain.  Conclusion: This is a rare case of MTB and IE in an immunocompetent patient, without severe valvular destruction. MTB although rare should remain on the differential especially in endemic countries and in patients reporting a long duration of symptoms. MTB and IE can present in the same patient and must be differentiated from TBE since the management of the case differs.